The Economics of Solicited and Unsolicited Credit Ratings - Fulghieri, Paolo; Strobl, Günter; Xia, Han (Review of Financial Studies, 2014)
This paper develops a dynamic rational expectations model of the credit rating process, incorporating three critical elements of this industry: (1) the rating agencies' ability to misreport the issuer's credit quality, (2) their ability to issue unsolicited ratings, and (3) their reputational concerns. We analyze the incentives of credit rating agencies to issue unsolicited credit ratings and the effects of this practice on the agencies' rating strategies. We find that issuance of unfavorable unsolicited credit ratings enables rating agencies to extract higher fees from issuers by credibly threatening to punish those that refuse to acquire a rating. Also, issuing unfavorable unsolicited ratings increases the rating agencies' reputation by demonstrating to investors that they resist the temptation to issue inflated ratings. In equilibrium, unsolicited credit ratings are lower than solicited ratings, because all favorable ratings are solicited; however, they do not have a downward bias. We show that, under certain conditions, a credit rating system that incorporates unsolicited ratings leads to more stringent rating standards.